La représentation du père Brown et du mal dans les nouvelles policières de G. K. Chesterton : The Innocence of Father Brown (1911), entre orthodoxie et hétérodoxie - Françoise Dupeyron-Lafay (Revue Française de Civilisation Britannique)
Chesterton’s choice of Father Brown, a Catholic priest, as the amateur detective of his short stories is not an orthodox one and the unflattering way in which he is portrayed is still less so, although the priest, inspired from a real-life model, turns out to be peerless. He embodies and voices the Christian values shared by his author. But despite the explicit orthodox message, an insidious, subliminal form of heterodoxy filters through: the representation of crime is highly aesthetic and the borderline between good and evil, sometimes blurred.